Central metal dependent modulation of induced-fit gas uptake in molecular porphyrin solids. Issue 56 (27th June 2018) - Nishihara, Hirotomo; Ohwada, Mao; Kamimura, Takuya; Nishimura, Masato; Tanaka, Hideki; Hiraide, Shotaro; Miyahara, Minoru T.; Ariga, Katsuhiko; Ji, Qingmin; Maruyama, Jun; Tani, Fumito
Abstract : Porphyrin-based supramolecular architectures exhibit induced-fit gas uptake, and moreover, the on–off porosity switching can be modulated simply by changing the central cation of porphyrin. Abstract : The induced-fit accommodation of a variety of gaseous molecules including non-polar molecules has been demonstrated in porphyrin-based supramolecular architectures for the first time. Moreover, the gas uptake behaviour can be modulated by changing the central cation of porphyrin.